2019
DOI: 10.3389/fpls.2019.00677
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Alleviates Oxidative Damages and Protects Photosystem II in Maize Seedlings Under Drought Stress

Abstract: The protective role of melatonin in plants against various abiotic stresses have been widely demonstrated, but poorly explored in organ-specific responses and the transmission of melatonin signals across organs. In this study, the effects of melatonin with the root-irrigation method and the leaf-spraying method on the antioxidant system and photosynthetic machinery in maize seedlings under drought stress were investigated. The results showed that drought stress led to the rise in reactive oxygen species (ROS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
155
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 83 publications
(117 reference statements)
27
155
1
1
Order By: Relevance
“…2). These results are consistent with Huang et al 52 and Ahmad et al 53 who reported that melatonin application alleviated the negative effects of oxidative stress and ROS production. Even at mild water stress (60% FC), a reduced Fv/Fm ratio was recorded in the two species, and a more intense water stress (40% FC) had a further negative effect on this physiological parameter (Fig.…”
Section: Resultssupporting
confidence: 92%
“…2). These results are consistent with Huang et al 52 and Ahmad et al 53 who reported that melatonin application alleviated the negative effects of oxidative stress and ROS production. Even at mild water stress (60% FC), a reduced Fv/Fm ratio was recorded in the two species, and a more intense water stress (40% FC) had a further negative effect on this physiological parameter (Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, growth and yield reductions by drought were alleviated significantly by different concentrations (50, 100, and 150 mM) of melatonin (Tables 2 and 3). Earlier studies have confirmed that melatonin acted as a growth regulator of plant and thus could increase growth parameters in various plants (Li et al (2015), Liu et al (2015), Ye et al (2016), Cui et al (2017), Kabiri et al (2018), and Huang et al (2019)). Melatonin treatment could alleviate the adverse effects of drought stress on M. oleifera plant via improving their growth and physiological attributes.…”
Section: Discussionmentioning
confidence: 85%
“…Melatonin could alleviate the harmful effects of oxidative damages on proteins, lipids, and nucleic acids via its role as ROS scavenger or by regulating nonenzymatic antioxidants or enzymatic antioxidant biosynthesis or activities (Li et al 2015). The improved role of melatonin on decreasing oxidative damage induced by water deficit has been proven earlier in different plant species of cucumber (Zhang et al 2014a), apple (Li et al 2015), soybean (Wei et al 2015), wheat (Sadak 2016a), Moldavian balm (Kabiri et al 2018), and maize (Huang et al 2019). Treatment of plants with melatonin enables plants to tolerate abiotic stress via enhancing the recovery potential (Tan et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin acts as a hormone in plants, and as a signaling molecule in a wide range of biological activities [5]. For example, melatonin treatment enhances plant tolerance against many stresses, including salt [6,7], drought [8,9], viruses [10], pathogens [11,12], waterlogging [13], and senescence [14], among others [15][16][17]. Melatonin is also involved in plant development processes such as growth [18,19], seed viability [20], flowering [21,22], endoplasmic reticulum (ER) quality control [23,24], secondary metabolite synthesis [25], and others [26].…”
Section: Introductionmentioning
confidence: 99%